2022
DOI: 10.3390/diagnostics12010187
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Ensemble Based on Radiomics to Predict BI-RADS Category and Reduce the Biopsy Rate of Ultrasound-Detected Suspicious Breast Masses

Abstract: We developed a machine learning model based on radiomics to predict the BI-RADS category of ultrasound-detected suspicious breast lesions and support medical decision-making towards short-interval follow-up versus tissue sampling. From a retrospective 2015–2019 series of ultrasound-guided core needle biopsies performed by four board-certified breast radiologists using six ultrasound systems from three vendors, we collected 821 images of 834 suspicious breast masses from 819 patients, 404 malignant and 430 beni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In this study, six types of texture features including GLCM, NGTDM, GLSZM, GLRM, GLDM, and First Order features were enrolled, and it was found that NGTDM and GLCM had similar weights. NGTDM quantifies the difference between a gray value and the average gray value of its neighbors within distance δ ( 30 34 ). Here, when we used NGTDM to evaluate the tumor ROI region, we also verified that NGTDM could accurately reflect tumor heterogeneity, thereby accurately predicting the NAC efficacy in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, six types of texture features including GLCM, NGTDM, GLSZM, GLRM, GLDM, and First Order features were enrolled, and it was found that NGTDM and GLCM had similar weights. NGTDM quantifies the difference between a gray value and the average gray value of its neighbors within distance δ ( 30 34 ). Here, when we used NGTDM to evaluate the tumor ROI region, we also verified that NGTDM could accurately reflect tumor heterogeneity, thereby accurately predicting the NAC efficacy in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The breast cancer patients with a total score of > 71.742 were more likely to achieve pCR after NAC. In recent years, the Nomogram prediction model has been widely used in the clinic ( 33 , 34 ). However, the indicators included in the Nomogram model for predicting the efficacy of NAC in breast cancer are confusing, and there is no conclusion on the evaluation time point of NAC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, combining prostate-specific antigen density and MRI for prostate biopsy planning allows the optimization of biopsy planning [ 110 ]. Interlenghi et al were even able to predict the BI-RADS category for suspicious breast masses using ultrasound radiomics and training-modified random forest classifiers, support vector machines, and k-nearest neighbor classifiers [ 111 ]. Further developments could even lead to radiomics replacing biopsy and facilitate therapeutic decisions by predicting BI-RADS category by imaging.…”
Section: Application and Evidence For Novel Imaging Biomarkers For Im...mentioning
confidence: 99%